Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.lwt.2019.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Wine quality rapid detection using a compact electronic nose system: Application focused on spoilage thresholds by acetic acid

Abstract: It is crucial for the wine industry to have methods like electronic nose systems (E-Noses) for real-time monitoring thresholds of acetic acid in wines, preventing its spoilage or determining its quality. In this paper, we prove that the portable and compact self-developed E-Nose, based on thin film semiconductor (SnO2) sensors and trained with an approach that uses deep Multilayer Perceptron (MLP) neural network, can perform early detection of wine spoilage thresholds in routine tasks of wine quality control. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 22 publications
(29 reference statements)
1
47
3
Order By: Relevance
“…O-NOSE performs the measurement process in three stages: concentration, data acquisition (the recorded data corresponds to 180 seconds with 18.5 Hz sample rate) and purge [1] . Each measurement corresponds to the time-dependent output voltages of each gas sensor converted to resistance values according to the voltage-divider scheme [5] and the corresponding load resistor ( ).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…O-NOSE performs the measurement process in three stages: concentration, data acquisition (the recorded data corresponds to 180 seconds with 18.5 Hz sample rate) and purge [1] . Each measurement corresponds to the time-dependent output voltages of each gas sensor converted to resistance values according to the voltage-divider scheme [5] and the corresponding load resistor ( ).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…To obtain spoiled samples, 13 of the 22 bottles were randomly selected and left opened for six months before starting the measurements (low-quality LQ wines). Besides, four bottles were opened two weeks before beginning the data collection (average-quality AQ wines), and the remaining five bottles were opened at the starting time of each measurement (high-quality HQ wines) [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This solution is interesting, since it does not require feature extraction from the data. Rodriguez et al [176] achieved a similar result with a deep multilayer perceptron neural network to identify wine spoilage in less than three seconds. Munoz-Mata et al [177] held the same reasoning with QCM sensors.…”
Section: A Model Of Neurons: Toward Spike-based Neuromorphic Approachesmentioning
confidence: 78%
“…Electronic tongue (e-tongue) and electronic nose (e-nose) offer a fast, low cost, and non-destructive alternative to detecting samples without sample preparation, [13][14][15]. E-tongue (e-nose) can simulate human gustatory (olfactory) evaluation process to evaluate food qualities via 'taste' (smell) information [16][17][18][19], and both the instrument has been used successfully for evaluating the wine quality [20][21][22][23][24]. Although the e-tongue and e-nose were not used for detecting the quality of Chinese rice wine, the successful usage of the instruments indicated that e-tongue and e-nose have technique potential for identifying the wine age of rice wines.…”
Section: Introductionmentioning
confidence: 99%